HPV vaccination uptake and administration from 2006 to 2016 in a commercially insured population of the United States - Vimalanand S. Prabhu; Neha Bansal; Zhiwen Liu; Rodney Finalle; Martin Sénécal; Smita Kothari; Kemar Trowers; Evan Myers (BMC, 2021)
Abstract Background Human papillomavirus (HPV) infection can cause various cancers and can be prevented through vaccination. The American Cancer Society (ACS) has set an HPV vaccination completion target in 13-year-old children to 80% by 2026. While HPV vaccine coverage (proportion ever vaccinated) estimates are available, annual uptakes (proportion initiating vaccine in a year) in the United States (U.S.) are not well-known. Methods We analyzed MarketScan® claims database to assess HPV vaccination uptakes in the U.S. among the 9- to 26-year-olds in 2006-2016. The annual uptake was the ratio of the number of enrollees who had a first record of an HPV vaccine during the year, and the number of enrollees of similar age and sex that year. Results Uptake was below 1% among children turning 9 and 10 years old during the year. Since 2009 among female and since 2013 among males, the annual uptake has been the highest in those turning 13 years old (19.7% among females and 17.6% among males in 2016). Catch-up vaccination among older adolescents and young adults increased after Advisory Committee for Immunization Practices (ACIP) recommendations, but eventually slowed down as more younger persons were vaccinated. Most young adolescents were vaccinated by pediatricians, whereas young adult women were predominantly vaccinated by obstetricians/gynecologists and young adult males by family physicians. While only about half of the adolescents had well-check visits, the majority of those who initiated HPV vaccination had one the same year. Conclusion Continued increase in uptake is needed to reach the ACS 2026 goals.